COMMITMENT DAN AGREEABLENESS DENGAN FORGIVENESS DALAM MENGHADAPI KONFLIK PADA DEWASA MUDA YANG MENJALIN HUBUNGAN - Shafa, Kinanthi Mutiara; Ekasari, Agustina; Muslimah, Alfiana Indah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2024)
Low forgiveness in a relationship when facing conflict cancause new conflicts and to be able to cause separation. Thisstudy aims to determine the relationship between commitmentand agreeableness with forgiveness in dealing with conflict inyoung adult in relationships. The method used in this study is aquantitative method with a correlational type. The subjects inthis study amounted to 151 men and women aged 18-25 yearswho were in a courtship/commitment relationship with theopposite sex for at least 6 months and had experiencedcommunication conflicts in their relationships. In this study,data collection used the original scale that had been translate.Measurements for forgiveness variables use TRIM-18(Transregression-Related Interpersonal Motivation),commitment variables using measuring tools made by Rusbult,and agreeableness variables using the Big Five Inventory (BFI)scale. The data analysis use to see the relationship betweenvariables in this study was the Spearman Rank correlation testand multiple linear regression assisted using the SPSS(Statistical Packages for Social Science) version 25 for windowprogram. This study found that there is a relationship betweencommitment and forgivness, agreeableness with forgiveness,and the influence of commitment and agreeableness onforgiveness